Infiltration Characteristics of Organic Amended Soils (Global Journals of Research in Engineering, 2016)
The infiltration characteristics of organic amended soil were studied for soils amended with cow dung (CM) and poultry litter (PM). The aim was to determine the effect of these amendments on the infiltration characteristics of the soil. A field size of 200 m2 was divided into three strips, 50 kg each of Cow dung and poultry litter was applied into the first and third strip and the middle strip served as control. Soil samples were taken from each strip for soil#x2019;s physical property determination, one week after manure application infiltration runs were made using the double ring infiltrometer from six points on each strip, and the tests were repeated three weeks and six weeks after manure application. Bulk density of CM and PM reduced by 15.5% and 33.2% respectively, the CM strip increased infiltration rate by 60 % relative to the Control while the PM strip increased infiltration rate by 29 %. T-test showed a high significant difference between the control and the amended strips, CM and PM strip increased cumulative infiltration depth by 61.4 % and 48.1%.
Keywords: poultry litters; cow dung